Evaluation of wear resistance and fluoride release from glass ionomer covered with nanofilled self-adhesive coat: An in vitro study - Zahra Lari; Fariba Ezoji; Hemmat Gholinia; Effat Khodadadi (Babol University of Medical Sciences, 2021)
Introduction: The resin-modified glass ionomer (RMGI) materials are hybrid materials including conventional glass ionomer and small addition resin. They have the advantages of both, such as adhesion to tooth structure, esthetics and fluoride release. The purpose of this study was to compare the fluoride release and wear resistance of two types of RMGI. Materials & Methods: In this in vitro study, specimens for measuring the fluoride release were made with brass mold from two types of RMGI EQUIA Forte glass ionomer and Fuji II conventional glass ionomer. After incubating the specimens in a plastic vial containing 7 ml of distilled water, the release of fluoride for each specimen was measured on days 1, 7 and 15 using a PH/Ion meter device. For evaluating the wear resistance, 8 specimens were prepared using a brass mold in each group. Then, each specimen was exposed to 5000, 10000, 20000, 40000, 80000 and 120000 cycles in wear simulator. The specimens' weight was measured by an electronic weight balance before and after each wear cycle. The data were analyzed by SPSS-17 through repeated-measurement ANOVA and independent T-test. Results: Fluoride released from Fuji II glass ionomer was significantly higher in the first 24 hours and on day 7. During the day 15, the differences in fluoride release between the two glass ionomer groups were not statistically significant. (p<0.001). The EQUIA Forte glass ionomer exhibited significantly greater wear resistance in different wear cycles. (p<0.001) Conclusion: Due to its good wear resistance, acceptable fluoride release, ease of clinical use and infection control, the capsular glass ionomer can be a useful material in people at high risk of caries, temporary restoration techniques, pediatric dentistry and root caries.